Products and Processes Emanated from BSR-NAIP for commercial application - Kochhar, Sudhir; Dar, Bilal Ahmad; Sarkar, Priyanka (Indian Farming, 2015)
The NAIP was successful in promoting strategic research to logical conclusions where at least commercial products besides other marketable research tools, like parentage detection kits in dairy cattle, buffalo, camel, sheep, goat, etc., could be made available within the Project period. This achievement is unprecedented in the ICAR funded extra-mural research support provided so far. Nevertheless,it provides a successful model for further encouragement and future application.